Femoral Vein Intravascular Synovial Sarcoma Mimicking Primary Deep Vein Thrombosis—A Rare Cause of Deep Vein Thrombosis - R. Jayakrishanan; Jineesh Valakkada; Anoop Ayyappan; Rajalakshmi Poyuran; Shivanesan Pitchai (Indian Journal of Radiology and Imaging, 2024)
Synovial sarcomas are rare malignant mesenchymal soft tissue tumors. We presented the case of a 53-year-old woman patient presenting with acute deep vein thrombosis, later diagnosed as a deep synovial sarcoma of the femoral vein wall. The tumor was identified through cross-sectional magnetic resonance angiography and computed tomography, followed by ultrasound-guided core biopsy. The case report emphasized the importance of considering the possibility of an intravascular neoplasm mimicking thrombus, particularly if calcifications, vein expansion with intravascular cystic spaces, fluid–fluid levels, and septations within a thrombosed vein are seen in imaging.